From outcome measurement to improving health outcomes after lower limb amputation—A narrative review exploring outcome measurement from a clinical practice perspective. Issue 4 (31st August 2022) - Ostler, Chantel; Scott, Helen; Sedki, Imad; Kheng, Sisary; Donovan-Hall, Margaret; Dickinson, Alex; Metcalf, Cheryl
Abstract : Outcome measurement is essential to understand the impact of clinical interventions and the performance of services. Despite national and professional body encouragement, and successful examples of system level outcome measurement within some health care settings, many barriers still exist preventing outcome measurement from becoming embedded in clinical practice. This paper presents a narrative review which aims to describe the state of the outcome measurement evidence base in prosthetic rehabilitation, as applied in clinical practice, with a view to identifying areas for future work aimed at making outcome measurement in prosthetic rehabilitation a meaningful reality. A literature search of four databases was undertaken, following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis principals appropriate to narrative reviews, and using the search terms outcome, measur*, tool, scale, instrument, prosthe*, amput* and limb loss. A total of 1116 papers were identified. Following screening 35 papers, focusing on four main themes, were included in the review. Themes were: 1) What outcome domains should be measured? 2) How can these outcome domains be measured? 3) What are the barriers to outcome measurement? and 4) What can be learnt from examples of ROM in prosthetic rehabilitation? Findings suggest that successful outcome measurement is multifaceted. Understanding and embedding value at every step appears to be key to success. Addressing the questions of 'what' outcome domains to measure and 'how' to measure them, may help establish consensus. Routine outcome measurement practice at the clinical level should ensure data collection is valuable to clinical practice, makes use of information technology solutions and has organisational engagement.